Biofilm Inhibition and Eradication Properties of Medicinal Plant Essential Oils against Methicillin-Resistant Staphylococcus aureus Clinical Isolates - Fethi Ben Abdallah; Rihab Lagha; Ahmed Gaber (MDPI AG, 2020)
Methicillin-resistant Staphylococcus aureus is a major human pathogen that poses a high risk to patients due to the development of biofilm. Biofilms, are complex biological systems difficult to treat by conventional antibiotic therapy, which contributes to >80% of humans infections. In this report, we examined the antibacterial activity of Origanum majorana, Rosmarinus officinalis, and Thymus zygis medicinal plant essential oils against MRSA clinical isolates using disc diffusion and MIC methods. Moreover, biofilm inhibition and eradication activities of oils were evaluated by crystal violet. Gas chromatography-mass spectrometry analysis revealed variations between oils in terms of component numbers in addition to their percentages. Antibacterial activity testing showed a strong effect of these oils against MRSA isolates, and T. zygis had the highest activity succeeded by O. majorana and R. officinalis. Investigated oils demonstrated high biofilm inhibition and eradication actions, with the percentage of inhibition ranging from 10.20 to 95.91%, and the percentage of eradication ranging from 12.65 to 98.01%. O. majorana oil had the highest biofilm inhibition and eradication activities. Accordingly, oils revealed powerful antibacterial and antibiofilm activities against MRSA isolates and could be a good alternative for antibiotics substitution.